El podcast como herramienta educomunicativa para fomentar el kichwa en la ciudad de Machala - Delgado Honores, Allison Francisca; Coyago Jimenez, Leydi Scarleth (Machala, Utmachala, 2023)
In Ecuador there are 14 indigenous nationalities, according to the National Institute of Statistics and Census INEC, which total approximately 1 million 100 thousand inhabitants who are distributed in local, regional and national organizations. However, some of the ancestral languages of these communities are being lost to such an extent that their intangible heritage (language) only prevails in their community or environment where they continue to speak them. However, it is understood that Kichwa is the predominant ancestral language in the country, with a greater number of Kichwa speakers in different cities, and yet, to date, and after more than a decade of the new Constitution, no clear public policies have been established to prevent and neutralice the risk of the disappearance of the culture of these peoples. In this context, the inhabitants of the city of Machala have little knowledge of this ancestral language and prioritize customs, traditions and foreign languages, devaluing their roots. In addition, there are no training programs or communication products that allow citizens in general to be motivated to learn Kichwa. One way to promote a new language is based on hearing and listening; therefore, the podcast is defined as a language teaching tool, it has been used on previous occasions to teach English and Quechua. Its audio format means that it is considered an effective and practical means of educational-communication learning. From this position, the research problem is born: How to promote the Kichwa language through a podcast as an educational-communication tool in the inhabitants of the city of Machala? In order to solve the problem, the following objective is proposed: To promote the Kichwa language through a podcast as an educational and communicational tool to enhance its learning in the inhabitants of the city of Machala. In this research we used data collection techniques such as interviews with several professionals and creators of podcast content, in order to gather information on the most appropriate way to create a communication product, the importance of it and know the benefits of teaching through audios. We also conducted surveys to the population of the city of Machala to know the degree of knowledge that people have about the language, especially young people and the acceptance of the final product, in this case a podcast. Finally, a focus group was carried out to assess the relevance of the proposal and an expert evaluation based on three parameters: the audio message, the production and methodology of a podcast. The population mostly interested in learning Kichwa through podcasts is between 16 and 25 years old; they are young people who see the product as an entertaining way to continue educating themselves, for them Kichwa is a way to identify themselves culturally and determine this language as relevant in the Ecuadorian culture. The population mostly interested in learning Kichwa through podcasts is between 16 and 25 years old; they are young people who see the product as an entertaining way to continue educating themselves, for them Kichwa is a way to identify themselves culturally and determine this language as relevant in the Ecuadorian culture. On the other hand, in the evaluation of the experts it was determined that the podcast is a dynamic product, with a capacity to teach in an interactive way, this educational-communicative tool is potentially useful to know, learn and strengthen the Kichwa language. The characteristic of its format makes its realization more feasible.
En Ecuador existen 14 nacionalidades indígenas, según el Instituto Nacional de Estadísticas y Censos INEC que suman aproximadamente 1 millón 100 mil habitantes que se encuentran distribuidos en organizaciones locales, regionales y nacionales. Sin embargo, algunas de las lenguas ancestrales de estas comunidades se están perdiendo a tal punto que su patrimonio intangible (lengua) solo prevalece en su comunidad o en su entorno donde las siguen hablando. En la región Costa se concentra solo el 8,3% de las comunidades indígenas, no obstante, se comprende que el kichwa es la lengua ancestral predominante dentro del país, con una mayor cantidad de kichwa hablantes en diferentes ciudades y aun así, hasta la presente, y luego de más de una década de vigencia de la nueva Constitución, no se han establecido políticas públicas claras que prevengan y neutralicen el riesgo de desaparición de la cultura de estos pueblos. En este contexto, en la ciudad de Machala sus habitantes tienen escasos conocimientos sobre esta lengua ancestral, priorizan costumbres, tradiciones y lenguas extranjeras desvalorizando sus raíces. Además de ello, no existen programas de formación o productos comunicacionales que permitan que la ciudadanía en general se motive a aprender el kichwa. Una manera de fomentar un nuevo idioma es basarse en el oído y la escucha; por ello, el podcast es definido como instrumento de enseñanza de idiomas, ha sido utilizado en ocasiones anteriores para enseñar inglés y el quechua. Su formato de audio, hace que sea considerado como un medio de aprendizaje educomunicacional efectivo y práctico. Desde esta postura nace el problema de investigación ¿Cómo fomentar la lengua kichwa a través de un podcast como herramienta educomunicacional en los habitantes de la ciudad deMachala? Con la finalidad de dar solución a la problemática, se plantea el siguiente objetivo: Fomentar la lengua kichwa a través de un podcast como herramienta educomunicacional para valorizar su aprendizaje en los habitantes de la ciudad de Machala. En la presente investigación se utilizó técnicas de recolección de datos como las entrevistas a varios profesionales y creadores de contenido podcast, con la finalidad de recopilar información sobre la forma más adecuada de crear un producto comunicacional, la importancia del mismo y conocer los beneficios de la enseñanza por medio de audios. También se realizó encuestas a la población de la ciudad de Machala para conocer el grado de conocimiento que tienen las personas sobre la lengua, especialmente los jóvenes y la aceptación hacia el producto final, en este caso un podcast. Finalmente se llevó a cabo un focus group para valorar la pertinencia de la propuesta y una evaluación de expertos basada en tres parámetros: el mensaje auditivo, la producción y metodología de un podcast. La población mayormente interesada para aprender kichwa por medio de podcast, se encuentra entre los 16 a 25 años, son jóvenes que ven el producto una forma entretenida de seguirse educando, para ellos el kichwa es una forma de identificarse culturalmente y determinan a esta lengua como relevante en la cultura ecuatoriana. Por otro lado, en la evaluación de los expertos se pudo determinar que el podcast es un producto dinámico, con una capacidad de enseñar de manera interactiva, esta herramienta Educomunicativa es potencialmente útil para conocer, aprender y afianzar la lengua kichwa. La Característica propia de su formato hace que sea más factible su realización.
Keywords: IDIOMA KICHWA; PODCAST; EDUCOMUNICACION; IDENTIDAD CULTURAL